2015
DOI: 10.1126/scitranslmed.aaa3787
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus NS1 triggers endothelial permeability and vascular leak that is prevented by NS1 vaccination

Abstract: The four dengue virus serotypes (DENV1 to DENV4) are mosquito-borne flaviviruses that cause up to ~100 million cases of dengue annually worldwide. Severe disease is thought to result from immunopathogenic processes involving serotype cross-reactive antibodies and T cells that together induce vasoactive cytokines, causing vascular leakage that leads to shock. However, no viral proteins have been directly implicated in triggering endothelial permeability, which results in vascular leakage. DENV nonstructural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
481
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(503 citation statements)
references
References 41 publications
(70 reference statements)
20
481
2
Order By: Relevance
“…Importantly, a dose-dependent release of proinflammatory cytokines, such as IL-6 and TNF-α, was observed in the S.Int. of the AG129 mouse model (35,36) in these studies. These observations support the present study, irrespective of whether AG129 mice were infected with a mouseadapted strain (17) or clinical isolate of DENV2 (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, a dose-dependent release of proinflammatory cytokines, such as IL-6 and TNF-α, was observed in the S.Int. of the AG129 mouse model (35,36) in these studies. These observations support the present study, irrespective of whether AG129 mice were infected with a mouseadapted strain (17) or clinical isolate of DENV2 (11).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, two independent studies reported the potential for the virus-encoded NS1 protein to directly contribute to dengue disease pathogenesis (35,36). The study by Modhiran and colleagues (35,36) demonstrated that NS1 is a pathogen-associated molecular pattern that recognizes TLR4 in target cells, which can lead to release of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanlaya et al also proposed that decreasing levels of vascular endothelial cadherin and Zonula occludens-1 in addition with alteration of actin assembly might be responsible for increased permeability in dengue virus-infected human endothelial cells (11). Recently, it was reported that treatment for recombinant dengue NS1 produced from human embryonic kidney 293 cells in human endothelial cell monolayers (HPMECs and HUVECs) caused disruption of endothelial cell permeability in a dose-and time-dependent manner (28). The authors also suggested that this effect might have been derived from the hexameric NS1 produced from eukaryotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that it generated lots of cross-reactive nonneutralzing/ enhancing antibodies. It has therefore been proposed that it is not only the presence of dengue neutralizing antibodies that may hold the key to a successful dengue vaccine candidate but also DENV serotype-specific neutralizing antibodies [44,45]. Therefore an effective dengue vaccine must be designed with the capability of inducing predominantly serotype-specific neutralizing antibodies (protective) in the absence of serotype cross-reactive neutralizing antibodies (disease enhancing) [46].…”
Section: Resultsmentioning
confidence: 99%